2010
DOI: 10.1073/pnas.1018022108
|View full text |Cite
|
Sign up to set email alerts
|

β Ca 2+ /CaM-dependent kinase type II triggers upregulation of GluA1 to coordinate adaptation to synaptic inactivity in hippocampal neurons

Abstract: Prolonged AMPA-receptor blockade in hippocampal neuron cultures leads to both an increased expression of GluA1 postsynaptically and an increase in vesicle pool size and turnover rate presynaptically, adaptive changes that extend beyond simple synaptic scaling. As a molecular correlate, expression of the β Ca 2+ /CaM-dependent kinase type II (βCaMKII) is increased in response to synaptic inactivity. Here we set out to clarify the role of βCaMKII in the various manifestations of adaptation. Knockdown of βCaMKII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 36 publications
9
59
0
Order By: Relevance
“…Expression of ΔEF‐Miro1 on the other hand suppressed any activity‐dependent changes in mitochondrial occupancy upon PTX and TTX treatment (Fig 4C and F). Inactivity induced by glutamate receptor blockade (APV: 100 μM, NBQX: 10 μM, 24 h), known to initiate presynaptic homeostatic plasticity due to a compensatory increase in presynaptic release probability 32, also resulted in a change in mitochondrial presynaptic occupancy (control 0.302 ± 0.02, APV + NBQX 0.214 ± 0.02, t ‐test * P < 0.05; Fig EV4F). These activity‐dependent changes were again inhibited following the expression of ΔEF‐Miro1 (control 0.256 ± 0.03, APV + NBQX 0.259 ± 0.05; Fig EV4H).…”
Section: Resultsmentioning
confidence: 98%
“…Expression of ΔEF‐Miro1 on the other hand suppressed any activity‐dependent changes in mitochondrial occupancy upon PTX and TTX treatment (Fig 4C and F). Inactivity induced by glutamate receptor blockade (APV: 100 μM, NBQX: 10 μM, 24 h), known to initiate presynaptic homeostatic plasticity due to a compensatory increase in presynaptic release probability 32, also resulted in a change in mitochondrial presynaptic occupancy (control 0.302 ± 0.02, APV + NBQX 0.214 ± 0.02, t ‐test * P < 0.05; Fig EV4F). These activity‐dependent changes were again inhibited following the expression of ΔEF‐Miro1 (control 0.256 ± 0.03, APV + NBQX 0.259 ± 0.05; Fig EV4H).…”
Section: Resultsmentioning
confidence: 98%
“…With the emerging role of CaMKIIβ in stabilizing F-actin, it appears likely that the homeostatic increase in synaptic strength is at least in part due to the CaMKIIβ-mediated increase in F-actin content, which in turn leads to larger spine size and thereby higher postsynaptic strength. Indeed, knock down of CaMKIIβ prevents the increase in postsynaptic GluA1 that is otherwise observed upon chronic inhibition of neuronal activity by TTX (Groth et al, 2011) and overexpression of CaMKIIβ increases mEPSC frequency likely by increasing synapse density (Thiagarajan et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…CaMKIIα overexpression in dissociated hippocampal cultures drastically decreases mEPSC frequency (but increases mEPSC amplitude) (Thiagarajan et al, 2002). CaMKIIβ overexpression increases GluA1 protein levels (Groth et al, 2011), the number of PSD-95 positive puncta (Fink et al, 2003), and mEPSC frequency (but not amplitude) (Thiagarajan et al, 2002). Overexpression of CaMKIIα might impair spine stability and thereby synapse number by reducing the interaction of the enzyme with F-actin due to decreased CaMKIIβ content in the dodecamer, while overexpression of CaMKIIβ might have the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that HSP-associated upregulation of GluA1 protein levels could be triggered by an increase in b Ca 2þ /calmodulin-dependent protein kinase II (bCaMKII) expression [13]. Because regulation of kinase activity of both a and b CaMKII isoforms strongly depends on autophosphorylation at Thr286 and Thr287, respectively (reviewed in [14]), we decided to assess whether heparinase treatment affects protein expression or autophosphorylation of these two major forebrain CaMKII isoforms in primary hippocampal neurons (figure 3b).…”
Section: (C) Biochemical Modifications After Heparinase Treatmentmentioning
confidence: 99%